Knowledge and Application of Mental Skills among First-Year Sports Coaching Education Students: A Cross-Sectional Survey at Universitas Negeri Makassar - Hamid, Muflih Wahid (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to explore the extent of mental skills exposure and understanding among first-year students enrolled in a Sports Coaching Education program, the majority of whom are athletes representing various regions in South Sulawesi. A descriptive research method with a cross-sectional survey design was used. The population consisted of 195 new students, with 171 valid responses obtained through an online questionnaire comprising both closed and open-ended questions. The data were analyzed using descriptive techniques and qualitative interpretation of open responses. Results show that while the students come from diverse sports backgrounds and levels of competitive experience, only a minority have received structured mental skills training. Most psychological guidance came informally from coaches, and upon further analysis, it was revealed that such guidance often involved physically intensive or disciplinary measures rather than scientifically grounded psychological techniques. Furthermore, a significant majority of the participants reported experiencing performance anxiety, loss of motivation, and diminished self-confidence before competitions, yet lacked the tools to manage these psychological challenges effectively. This study underscores the importance of introducing structured mental skills training early in athletes’ careers and integrating sport psychology into coaching education programs. By doing so, future coaches will be better equipped to foster both performance and psychological well-being in athletes under their guidance